Integration of Artificial Intelligence Literacy into a Transdisciplinary Curriculum to Enhance Students’ Critical Thinking Skills - Ira Kurniati; Maulana Teguh Perdana; Heny Indriani; Laxmi (Khazanah: Journal of Islamic Education and Science, 2025)
This study was motivated by the increasing use of artificial intelligence in higher education, which had not been systematically integrated into the curriculum to support the development of students’ critical thinking skills. The study aimed to analyze the pattern of artificial intelligence literacy integration within a transdisciplinary curriculum and to identify its impact on enhancing students’ critical thinking abilities. A qualitative approach with a case study design was employed in interdisciplinary study programs at a higher education institution. Data were collected through curriculum document analysis, classroom observations, in-depth interviews with lecturers and students, and examination of academic assignments and portfolios. Data were analyzed thematically through processes of data reduction, categorization, data display, and interactive conclusion drawing. The findings indicated that the integration of artificial intelligence literacy, designed through reflective and collaborative pedagogical approaches, contributed to improvements in analytical skills, information evaluation, critical argumentation, and students’ ethical awareness. This study produced a transdisciplinary curriculum-based model of artificial intelligence literacy integration that enriched the development of higher-order thinking skills in higher education contexts.